Energy-Exergy Performance Comparison of an Ideal Vapor Compression Refrigeration Cycle using Alternatives Refrigerants of R134a for Low Potential of Global Warming - Al-Sayyab, Ali Khalid Shaker (Basrah Journal for Engineering Sciences, 2017)
This work presents a theoretical study on the application of low global warming refrigerants as alternative refrigerant to R 134a in a refrigeration system. The refrigerants investigated are R1234yf, R1234ze, R245fa and R227ea. The performance characteristics of the refrigeration system were predicted using mathematical models running by using EES program under different condenser and evaporator temperatures. The results show that at any working condition the R1234ze give identical performance to R134a and can be used as the best low global warming alternative refrigerant. So the compressor work with R1234ze should be designed with displacement volume more than that of R134a to overcame the reduction in mass flow rate.